Identification of hazardous road sites: a comparison of blackspot methodology of Narogong Road Bekasi and Johor Federal Roads - Isradi, Muhammad; Dwiatmoko, Hermanto; Prasetijo, Joewono; Rifai, Andri Irfan; Zainal, Zaffan Farhana; Zhang, Guohui; Firdaus, Hendy Yusman (Universitas Mercu Buana, 2024)
A traffic accident is an unexpected and inadvertent road event involving a vehicle with or without other road users that results in human injuries and possibly property damage. This study identifies and analyses the characteristics of Indonesian and Malaysian road traffic incidents. The method used was the identification of crash data coordinates and the Equivalent Accident Number (EAN) score per road segment. Accident characteristics are based on the type of road traffic accident, and collision is the most common type of accident. Speed data of two vehicles, cars and motorcycles, was collected through the test driver method by using the same vehicles for cars and motorcycles and following their normal driving habits. From the analysis results, some factors causing accidents on the Bekasi Narogong Road Section are the lack of traffic signs, road surface conditions, and lack of clear road markings. While on the FT050 Johor federal road, every kilometre per segment and along the segment, motorcycles are faster than cars in terms of speed.